Eksplorasi Gastronomi Etnis Makassar Melalui Penyajian Rijsttafel Pada Hidangan Kebudayaan Masyarakat Gantarangkeke Kabupaten Bantaeng Sulawesi Selatan - Dewi Andriani; St. Hadijah; Mudrifah Amaliah; Sherry Adelia Natsir Kalla (Journal on Education, 2024)
The gastronomy presented by the people of Bantaeng has a very diverse heritage from Makassar tribe and required a creative process in its introduction. Through exploration that combines the presentation of Rijsttafel which has been know since the Dutch colonial era, we create a variety of local culinary riches. This research measure the public’s acceptance of the the Makassar tribe’s culinary delights in Gantarangkeke village, Bantaeng Regency by using Rijsttafel serving which is distributing various types of dishes on the dining table with hedonic test through aspects of assessing taste, texture, color and aroma with Likerts scale. The sampling technique used a non-probability sampling technique, namely purposive sampling with the criteria of 50 untrained panelists. The research results showed that the level of preferene for each type of food was Rakang 4,28; Kaloli’ 4,37; Karemanaci’ 4,58; Gagape’ 4,42; Gangang Pacco’ 4,42 and Kopi Langi’ 4, 61. With score above 4,00, the level of panelist’s acceptance of the gastronomi culinary of Makassar tribe in Gantarangkeke Village is accepted by the community.